Normobaric hypoxic training model for youth bench shooting sport: effects on intellectual efficiency verified by psycho-physiological functionality test - Tambovtseva, R. V.; Danilov, D. V.; Sechin, D. I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to analyze benefits of normobaric hypoxic training model for intellectual efficiency in youth bench shooting sport using psycho-physiological functionality tests. Methods and structure of the study. The study was run at the N.I. Volkov Sports Biochemistry and Bioenergetics Department Laboratory of Russian State University of Physical Education, Sports, Youth and Tourism (SCOLIPE). We sampled junior bench shooters (n=40) on their informed written consent and split them up into RG (trained traditionally) and EG (trained using hypoxic training method). The normobaric hypoxic training model implied a 30-minute inhaling of a gas mixture in a quiescent state using Everest-1 (model 7) Hypoxic Trainer system that generates 10-plus l/min of the gas mixture with 10-16% of oxygen. The sample was tested by computerized Sports Psycho-physiologist Test System to generate a range of psycho-physiological test rates including intellectual efficiency. The Sports Psycho-physiologist Test set included: the angular speed valuation; segments valuation; segments metering; angle valuation; and angle perception tests; plus the following sensorimotor response tests: right hand: response to light time; response to sound time; choice reaction; right leg response to light time; response to sound time; and right hand / right leg tapping test; and the left hand response to light time; response to sound time; choice reaction; left leg response to light time; response to sound time; and left hand / left leg tapping test. The tests were designed to prevent the monotony-related fatigue. Results and conclusion. The tests and analysis found the key variations in the psycho-physiological test rates with hypoxic training in the junior bench shooting sample. We found that the hypoxic training tends to speed up some sensorimotor responses and slow down a few motor functions. The test data arrays showed both positive and negative aspects of hypoxic training on the psycho-physiological functionality. The study findings may be recommended for consideration in the initiatives to use hypoxic training as an ergogenic tool in the bench shooting training systems.